Comparison of Transverse Mattress Vs Continuous Suture Urethroplasty in Tubularized Incised Plate Hypospadias Repair: A Prospective Study - Haq, Mahwish Noor ul; Bashir, Muhammad Kashif; Aman, Nadir; Rafiq, Hafiza Mariam; Yousaf, Abdullah; Zafar, Zuha (Indus Journal of Bioscience Research, 2025)
We studied two improved techniques for tabularized incised plate (TIP) repair in distal hypospadias: continuous vs transverse mattress sutures. We evaluated their effects on complications and surgical success. Material and Methods: We performed a prospective randomized trial on 60 boys with primary hypospadias, ages 1 to 13 years ( mean age 5.6 years), between June 2024 and November 2024. The participants were randomly divided into two groups based on suturing technique: continuous (30 boys) or transverse mattress(30 boys). This study aimed to compare the complication rates between two groups of patients, all of whom underwent the same preoperative, operative and follow up procedures, allowing for a direct comparison of outcomes. Results: Our study revealed no significant difference( p = 0.06) in complication rates between Group A and Group B. A total of 28 (46.7%) complications occurred, with 18 (30%) in Group A and 10 (16.7%) in Group B. The most common complication encountered in both groups was urethrocutaneous fistula (UCF), affecting nearly a quarter of the total patients. Specifically, 15%(9) of patients in Group A and 8.3%(5) of patients in Group B developed this complication, with a total of 14(23.3%) patients out of 60 being affected. Additionally, 6(10%) patients experienced wound dehiscence , 4(6.7%) in Group A and 2(3.3%) in Group B. Total 8(13.3%) patients developed meatal stenosis , 6 (10%) in Group A and 2 (3.3%) in Group B. Conclusion: The suture technique used in Snodgrass hypospadias repair doesn’t impact complication rates. Surgeon preference, not technique, should guide decision-making. This simplifies surgical planning, enhances patient outcomes and improves safety. Streamlining protocols benefits both patients and surgeons.